Taijiquan, estilo Yang clásico. Método completo y qigong. - Juan Pan González (Universidad de León, 2012)
Yang Jwing-Ming. Móstoles (Madrid): Arcano Books, 2005. 376 páginas. 24x17 cm. I.S.B.N.: 978-84-96111-37-0.